Structural Basis for Monoclonal Antibody Therapy for Transthyretin Amyloidosis - Avi Chakrabartty (MDPI AG, 2024)
The disease of transthyretin (TTR) amyloidosis (ATTR) has been known since the 1960s, and during the past 60 or so years, there has been a sustained period of steady discoveries that have led to the current model of ATTR pathogenesis. More recent research has achieved major advances in both diagnostics and therapeutics for ATTR, which are having a significant impact on ATTR patients today. Aiding these recent achievements has been the remarkable ability of cryo-electron microscopy (EM) to determine high-resolution structures of amyloid fibrils obtained from individual patients. Here, we will examine the cryo-EM structures of transthyretin amyloid fibrils to explore the structural basis of the two monoclonal antibody therapies for ATTR that are in clinical trials, ALXN-2220 and Coramitug, as well as to point out potential applications of this approach to other systemic amyloid diseases.